(untitled) (Fiep Bulletin - online, 2014)
The proposal of this study was to analysis the correlation of the deformity’s postural of knee and of “Q” angle with chondromalacia patellar in individual’s carriers of chondromalacia patellar. The research was carried through in the sector of physiotherapy of the clinics in study in the period of February to May. Twenty-eight (28) individuals where analyzed that they possessed the diagnostic of chondromalacia patellar. Of these, 61% of feminine sex and 39% of the masculine sex, with average age of 28 years. An evaluation was performed, which was anamneses and physical examination, where this test consisted of Waldron, postural deformities evaluation of the knees and measure the angle "Q". For the analysis of the data was used to test non parametric Fisher’s Exact. By making the correlation of test Waldron with chondromalacia patellar, that presented significance (p = 0,039). The same happened in pain retropatelar correlation with chondromalacia (p <0.001). When conducted on the correlation angle "Q" with chondromalacia, this has not produced significance (p = 0,519). In correlation knee flexo or recurve with chondromalacia patellar, there was no significance (p = 0,161). The same happened to make the correlation with chondromalacia patellar of the knee varus or valgus (p = 0,611). From these results we conclude that the test is Waldron efficiently to test the chondromalacia patellar, and that the increase in the Q angle and postural deformities of the knees, are not the only variables to be analyzed by the physiotherapist